An Advantage for Perceptual Edges in Young Infants' Memory for Speech. (September 2016) - Hochmann, Jean‐Rémy; Langus, Alan; Mehler, Jacques
Abstract : Models of language acquisition are constrained by the information that learners can extract from their input. Experiment 1 investigated whether 3‐month‐old infants are able to encode a repeated, unsegmented sequence of five syllables. Event‐related‐potentials showed that infants reacted to a change of the initial or the final syllable, but not to a change of the third, internal, syllable. The information carried by the internal constituents of a continuous speech sequence remains thus largely inaccessible at 3 months, whereas the information carried by perceptual edges may play a major role in the early steps of language acquisition. In Experiment 2, the preliminary analysis of a corpus of infant‐directed speech showed that the statistical information carried at utterance edges does not differ substantially from that contained in the whole input. Focusing on perceptual edges may thus facilitate the extraction of statistical information, by highlighting a representative sample of the input.